Short Communication: The Base “G” in TB86 Primer Frequently Used in the Amplification of katG Isoniazid Resistance Gene of Mycobacterium tuberculosis is an Insertion - Khan, Muhammad Mumtaz; Ali, Sajid; Kamal, Mustafa (Journal of Basic & Applied Sciences, 2012)
Tuberculosis is a re-emerging disease caused by Mycobacterium tuberculosis and isoniazid is the major drug used in chemotherapy to treat this infection. The mutations detected in katG gene are usually responsible for resistance in Mycobacterium tuberculosis. In our work, we have found that the primer TB86, usually used to amplify the katG gene, has an insertion when compared to katG gene of H37Rv.